2006
DOI: 10.1038/sj.jcbfm.9600332
|View full text |Cite
|
Sign up to set email alerts
|

From Homogeneous to Fractal Normal and Tumorous Microvascular Networks in the Brain

Abstract: We studied normal and tumorous three-dimensional (3D) microvascular networks in primate and rat brain. Tissues were prepared following a new preparation technique intended for high-resolution synchrotron tomography of microvascular networks. The resulting 3D images with a spatial resolution of less than the minimum capillary diameter permit a complete description of the entire vascular network for volumes as large as tens of cubic millimeters. The structural properties of the vascular networks were investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
129
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 103 publications
(137 citation statements)
references
References 31 publications
5
129
1
Order By: Relevance
“…A hysteresis thresholding method was used for the binarization step. Some morphological mathematical opening/ closure procedures were then used to finalize this step, so as to remove black islands inside white vessels (Risser et al, 2007). The vessel's density, volume, and length, which is obtained after this procedure, has been recently found consistent with other reported measures in primate and rodents (Risser et al, 2009;Tsai et al, 2009).…”
Section: Image Acquisition and Segmentationmentioning
confidence: 69%
See 3 more Smart Citations
“…A hysteresis thresholding method was used for the binarization step. Some morphological mathematical opening/ closure procedures were then used to finalize this step, so as to remove black islands inside white vessels (Risser et al, 2007). The vessel's density, volume, and length, which is obtained after this procedure, has been recently found consistent with other reported measures in primate and rodents (Risser et al, 2009;Tsai et al, 2009).…”
Section: Image Acquisition and Segmentationmentioning
confidence: 69%
“…To our knowledge, this issue has not been clearly discussed in earlier studies (Reichold et al, 2009). In the case of brain vessels, earlier investigations have shown that a representative elementary volume can be identified in primate cortex (Risser et al, 2007). The length scale associated with statistical decorrelation of the spatial distribution of the brain's microvascular networks has been found to be within 50 to 80 mm.…”
Section: Boundary Condition Implementationmentioning
confidence: 92%
See 2 more Smart Citations
“…3C). These statistics can be readily compiled and many have been published (13). We note that nðδÞ for normal tissues rises to a peak and then drops quickly as the maximum distance from a vessel is approached.…”
Section: Computational Models Of Diffusion Based On High-resolution Imentioning
confidence: 99%